A Feasibility Study of SCADA Implementation at an Indonesian Oil Company - Tungkagi, Hence; Saragih, Jenry Doan; Lubis, Rizky Dwi Prayogo; Syamil, Ahmad (Jurnal Ilmiah Mandala Education (JIME), 2021)
The implementation of Supervisory Control and Data Acquisition (SCADA) will make an activity more efficient because it will help control operation and production processes; control can be applied appropriately and at any time (real-time). This process will undoubtedly help the company to get maximum benefits. In 2020, the world oil price was very volatile and had touched a negative level. It is predicted that the uncertainty and low oil price will continue in the next few years. PT Pertamina Hulu Energi - Offshore South East Sumatra (PHE OSES), an Indonesian national company, plans to fully apply the SCADA system in its operational and production areas, because currently most of the PHE OSES areas still use the manual system. SCADA's estimated investment value of USD 8.6 million is a major investment for the company amidst the uncertainty of oil prices. Therefore, this project must get attention starting from the preparation, installation and implementation stages. In this article, economic analysis, cost & benefit analysis, and sensitivity test to factors that can affect economic value will be carried out. An analysis will also be carried out in terms of change management. All of these analyzes will answer whether the implementation of SCADA is feasible or not. The result of this research show that this project is feasible to be implemented in PHE OSES, it meets the capital budgeting criteria and has benefit to cost ratio larger than one. Oil price and oil losses recovery are the most affecting factors in the project’s feasibility. Company must do training, socialization, and hiring of experts play the vital role in the success of this project.